Perceived immigration. A case study for the municipality of Pozzuolo - STELLA, MARIANNA (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2011)
This study explores the perception of the residents of the municipality of Pozzuolo del Friuli, in the province of Udine, with regard to the phenomenon of foreign immigration to Italy. The study has involved a demoscopic survey conducted through a self-administered questionnaire, consisting of 60 questions divided in three thematic sections. The questionnaire was distributed by mail to a randomly-chosen population sample estimated in 10% of the total residents, proportionately distributed among the municipality main centre (Pozzuolo) and surrounding localities. The answers were analysed by the statistical software “Statistical Package for Social Science”. The results presented in this paper constitute a fraction of the total answers, which, in the cases of interest, have been cross-checked to provide a complete and detailed picture of the residents’ perception of the phenomenon. The study reveals an interest in immigration-related issues which is generally greater among younger people and for the nearest geographical contexts, and conversely less significant among older respondents and for the most distant geographical areas. The values of solidarity and hospitality are both considered significantly important by respondents, who show a greater propensity for the former over the latter. However, answers indicate that the two sentiments are directed at different categories of people: while solidarity may be shown with “anyone”, respondents feel most hospitable towards those who are closest to them. Moreover, attention has been paid to the analysis of the characteristics of foreign immigrants, such as their country of origin, religion, qualifications, and reason to emigrate, this last one being the variable which is most taken into account by the native respondents. It has also emerged that the immigrants’ country of origin, even if it does not appear to have influence over the acceptance, or lack of it, of a foreign person, is still relevant in determining the attitude of the native population. Regarding this, answers show that the preference given to areas of origin such as Western Europe and North America is accompanied by a tendency to reject immigrants coming from the Arab countries; the order of preference of the geographical areas is maintained unaltered for all the different categories of social relation proposed by the survey. In brief, even though native respondents have a propensity to prefer situations which are nearest to their own, they maintain a fundamental openness which encourages them to enter in contact with a foreign person without, at the same time, losing control over their environment and living space.